Radiation induced valvulitis with late leaflet rupture. Issue 6 (1st December 2001) - Katz, N M; Hall, A W; Cerqueira, M D
Abstract : Various cardiac sequelae of mediastinal irradiation have been reported, from pericarditis to conduction defects. Despite the potentially fatal nature of some of these abnormalities, many may present with few or no symptoms. In this case report, the patient, who had received 4000 rads to the mediastinum 24 years previously, presented with worsening shortness of breath and two episodes of lightheadedness. Subsequently, he was found to have aortic valve rupture associated with fibrosis. A review of the literature indicates that valve rupture is a novel consequence of mediastinal radiation.